SISTEM PENGUPAHAN PEKERJA PADA PERUSAHAAN KONVEKSI PT WEDANATA INDUSTRI NUSANTARA DI KABUPATEN BADUNG BALI - Dwipayanti, Cokorda Istri Putri; Apriliani, Kadek (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Obtaining a job and livelihood worthy of humanity is the right of every citizen which is a basic need for citizens. The employment relationship that has been established by workers and employers is created after an agreement between workers and employers, whether it is made in writing or unwritten, but the most important thing in the agreement will be stated by workers about their willingness to work for employers by receiving a number of wages. A systematic method and certain framework of thought aimed at studying and analyzing a legal phenomenon to then attempt a solution to the problems arising in the symptom in question. The wage system of the company PT Wedanata Industri Nusantara applies a wage system based on units of output and a monthly payment wage system, there are delays in paying workers' wages.